Children’s Participation In Khat Production In Mbeere: Drivers, Consequences And Remedies - Faith Mukami Ngari (Information Technology and Science (ITScience), 2026)
Khat is grown for the production of young tender twigs which are chewed for their stimulating effects. For a very long time, khat production has been taking place in the Nyambene hills, North East of Mount Kenya. Currently, the khat industry is no longer the sole preserve of the Meru. Rather it has become a multiethnic phenomenon; as khat plantations have sprung all over Embu County. Its consumption too is on the increase. Because of this, the marketing and distribution is sufficiently flexible to allow a large number of people to engage in the business and make a living from khat, thus the children have not been left out. Khat requires very frequent harvests and this therefore, calls for adequate labour so that it can be picked, packaged and transported very fast hence the involvement of children in its picking. Although children are expected to work within the family setting where they assist with the household chores and farm work as a way of socialization, concerns have been raised over primary school children’s participation in khat production. On one hand, their participation helps to uplift the household economy while at the same time affecting their education. This is a review paper that describes the push and pull factors responsible for children’s participation in khat production and the consequences of their involvement. Going forward the paper suggests measures to safeguard children from the identified adverse consequences of their involvement.